Apathy as a feature of prodromal Alzheimer's disease: an FDG‐PET ADNI study1. (20th June 2014) - Delrieu, Julien; Desmidt, Thomas; Camus, Vincent; Sourdet, Sandrine; Boutoleau‐Bretonnière, Claire; Mullin, Emmanuel; Vellas, Bruno; Payoux, Pierre; Lebouvier, Thibaud; Alzheimer's Disease Neuroimaging Initiative
<x xml:space="preserve">Abstract</x> Objective The goal of this study is to evaluate brain metabolism in mild cognitive impairment (MCI) patients with and without apathy (as determined by the Neuropsychiatric Inventory Questionnaire). Methods Baseline data from 65 MCI participants (11 with apathy and 54 without) from the Alzheimer's Disease (AD) Neuroimaging Initiative study were analyzed. All participants underwent a comprehensive cognitive and neuropsychiatric assessment, volumetric MRI and measures of cerebral glucose metabolism applying 18F‐fluorodeoxyglucose positron emission tomography at baseline. The presence of apathy at baseline was determined by the Neuropsychiatric Inventory Questionnaire. Results There was no difference between apathy and apathy‐free MCI patients regarding cognitive assessment and neuropsychiatric measures when apathy‐specific items were removed. Cerebrovascular disease load and cerebral atrophy were equivalent in both groups. Compared with the apathy‐free MCI patients, MCI patients with apathy had significantly decreased metabolism in the posterior cingulate cortex. Conclusion The presence of apathy in MCI patients is associated with AD‐specific pattern of brain metabolic defect. These results could suggest that apathy belongs to the spectrum of prodromal AD symptoms. Copyright © 2014 John Wiley & Sons, Ltd.